Oral anticoagulants after heart transplantation - comparison between vitamin K antagonists and direct oral anticoagulants - Darche, Fabrice Fernand; Fabricius, Lisa; Helmschrott, Matthias; Rahm, Ann-Kathrin; Ehlermann, Philipp; Bruckner, Thomas; Sommer, Wiebke; Warnecke, Gregor; Frey, Norbert; Rivinius, Rasmus (Journal of Clinical Medicine, 2023)
Aims: Patients after heart transplantation (HTX) often require oral anticoagulants (OACs) due to atrial arrhythmias or thromboembolic events but little is known about the post-transplant use of direct oral anticoagulants (DOACs). We investigated the frequency, indications, and complications of DOACs and vitamin K antagonists (VKAs) after HTX. Methods: We screened all adult patients for the use of post-transplant OACs who underwent HTX at Heidelberg Heart Center between 2000 and 2021. Patients were stratified by type of OAC (DOAC or VKA) and by DOAC agents (apixaban, dabigatran, edoxaban, or rivaroxaban). Indications for OACs comprised atrial fibrillation, atrial flutter, pulmonary embolism, upper and lower extremity deep vein thrombosis, as well as intracardiac thrombus. Results: A total of 115 of 459 HTX recipients (25.1%) required OACs, including 60 patients with DOACs (52.2%) and 55 patients with VKAs (47.8%). Concerning DOACs, 28 patients were treated with rivaroxaban (46.7%), 27 patients with apixaban (45.0%), and 5 patients with edoxaban (8.3%). We found no significant differences between both groups concerning demographics, immunosuppressive drugs, concomitant medications, indications for OACs, ischemic stroke, thromboembolic events, or OAC-related death. Patients with DOACs after HTX had a significantly lower one-year rate of overall bleeding complications (p = 0.002) and a significantly lower one-year rate of gastrointestinal hemorrhage (p = 0.011) compared to patients with VKAs after HTX in the Kaplan-Meier estimator. Conclusions: DOACs were comparable to VKAs concerning the risk of ischemic stroke, thromboembolic events, or OAC-related death but were associated with significantly fewer bleeding complications in HTX recipients.